Shells of the Roman snail are important microhabitats for soil invertebrates - Claudia Tluste (Senckenberg Gesellschaft für Naturforschung, 2021)
Shells of molluscs from snail farms (heliciculture) are used as food additives or construction material and ecological engineering approaches utilize their potential to assist with ecosystem restoration. Previous studies, for example, highlighted the importance of snail shells as microhabitat for threatened arthropod species with particular focus on wild bees nesting in empty shells. This study focuses on shells of the Roman snail (Helix pomatia Linnaeus, 1758) and their value as microhabitat for shell adopters in different dominant vegetation forms and sample periods. In total, 1408 empty shells were placed in areas dominated by one of two vegetation forms (herbaceous vegetation or trees) from February to November 2019 (autumn) or from February to June/July 2020 (summer). All collected shells (N = 618) were sealed at the time of collection, frozen and all content was then analysed with a digital microscope. In total, 91.4 % of all collected shells were occupied and the average number of shell adopters was 1.5 time higher in shells collected in summer compared to shells collected in autumn. The number of shell adopters per shell was 1.5 times higher in study areas dominated by herbaceous vegetation compared to study areas dominated by trees. Shell width, but not shell height significantly affected the composition of shell adopter communities. Shells with a larger width were more frequently colonized by another gastropod species [Discus rotundatus (O. F. Müller, 1774)] than less wide shells. Shells of the Roman snail provide important multipurpose benefits for a wide range of soil organisms, particularly in habitats that were dominated by herbaceous vegetation and in summer. In autumn, shell adopters included isopods, gastropods and spiders in one subset of shells or Collembola in another subset. The future use of commercially available, empty shells from heliciculture in local restoration projects of open, tree-free areas, holds the potential to support a diverse invertebrate fauna with additional refuge habitats.